A Study on Drone Design for Packages Delivery Services - Abdul Wahab Hashim, Muhammad Zaid; Hassan, Mohd Fahrul (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Drone or well-known as unmanned aerial vehicles is a flying robot in which are controlled autonomously using remote control. Drone technology have been seen to be applicable in various application such as in the transportation industry. The aim of this study is to investigate the possibilities of drone to ease item delivery for courier services. The use of drone in courier services will shorten the time taken to deliver goods. The objectives that needed to be achieved in this study are to identify the parameters involved in developing a drone for courier services. The development of drone must be able to lift and resist a minimum 5 kg of payload. The design of drone is analyzed by simulation which are performed by using SolidWorks software. A 3D CAD model of the drone was also developed by SolidWorks software. This project was performed using George E. Dieter’s approach as a guide. The cost estimation for the propose drone design is about RM 14 247.46. The drone is weighted at 20.1328 kg and the overall dimension of the drone is 1065.45mm in length and width, and 432mm in height. In conclusion, the drone for package’s delivery service has been designed and theoretically functioned.